2011
DOI: 10.1093/cvr/cvr132
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological response of human cardiomyocytes derived from virus-free induced pluripotent stem cells

Abstract: Virus-free hiPSCs differentiate efficiently into cardiomyocytes with cardiac-specific molecular, structural, and functional properties that recapitulate the developmental ontogeny of cardiogenesis. These results, coupled with the potential to generate patient-specific hiPSC lines, hold great promise for the development of an in vitro platform for drug pharmacogenomics, disease modelling, and regenerative medicine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
52
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 86 publications
(59 citation statements)
references
References 44 publications
7
52
0
Order By: Relevance
“…27 Several reports have demonstrated that hiPS-CMs at day 20 to 40 of differentiation have electrophysiological properties and respond to ion channel blockers. [12][13][14] In the present study, electrophysiological responses to ion channel blockers in d30CMs were similar to those in d60CMs and d90CMs, although the sensitivity to the calcium channel blocker was weaker. These functional assays showed that functions related to the β-adrenergic pathway and electrophysiological properties in hiPS-CMs did not change markedly until day 90 of differentiation.…”
Section: Discussionsupporting
confidence: 72%
“…27 Several reports have demonstrated that hiPS-CMs at day 20 to 40 of differentiation have electrophysiological properties and respond to ion channel blockers. [12][13][14] In the present study, electrophysiological responses to ion channel blockers in d30CMs were similar to those in d60CMs and d90CMs, although the sensitivity to the calcium channel blocker was weaker. These functional assays showed that functions related to the β-adrenergic pathway and electrophysiological properties in hiPS-CMs did not change markedly until day 90 of differentiation.…”
Section: Discussionsupporting
confidence: 72%
“…The FDA has thus recognised QT prolongation as an important variable which needs to be addressed during drug development while the International Conference of Harmonisation (ICH) Expert Working Group (EWG) for drug development has placed risk assessments for delayed ventricular repolarisation as standard procedure of preclinical evaluation of new chemical entities 24 . Cardiomyocytes differentiated from hPSCs open a new paradigm in regenerative medicine 25,26 , disease modelling 20,27 , drug discovery [18][19][20]28 and understanding developmental phenomena 17,29 . Similar to their adult counterparts, hPSC-derived cardiomyocytes express cardiac genes, structural proteins and ion channels 17,30 as well as exhibit a functional excitation-contraction coupling system which could be modulated through β1/β2-adrenergic and muscarinic receptor agonists 31 .…”
Section: Human Pluripotent Stem Cells and Drug Discovery: A New Beginmentioning
confidence: 99%
“…A number of studies have demonstrated the potential application of hPSCcardiomyocytes in evaluating pharmacological safety 23,[32][33][34][35][36] . For example, while E-4031 (I Kr blocker) and Satalol (class III anti-arrhythmic agent; I Ks blocker) were reported to induce QT prolongation, administration of quinidine (class I anti-arrhythmic agent; I Na blocker) and TTX (Na + channel blocker) resulted in a dose-dependent reduction in conduction velocity 18,32 . With the establishment of hiPSC technology, patientspecific cardiomyocytes could be generated, providing unprecedented insight into the molecular mechanisms surrounding disease pathogenesis 20 .…”
Section: Human Pluripotent Stem Cells and Drug Discovery: A New Beginmentioning
confidence: 99%
See 2 more Smart Citations